Porous laser-induced graphene electrode, preparation method, product and application
Through the preparation and modification of the graphene electrode induced by porous laser, the problems of low detection sensitivity and poor repeatability of bisphenol A in the prior art are solved, and the rapid, sensitive and reliable detection of bisphenol A is achieved, which is suitable for the detection of actual environmental samples.
Patent Information
- Application Number
- CN202411745533.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-02
- Publication Date
- 2025-03-11
AI Technical Summary
The prior art has problems such as narrow detection range, low sensitivity, poor repeatability and expensive instruments when detecting phenolic compound bisphenol A, which makes it difficult to achieve fast, sensitive and reliable detection.
The LIG material was prepared by using a porous laser-induced graphene electrode and a laser direct writing organic polymer film was used to prepare a LIG material, and its dispersion was modified on the surface of the substrate electrode to form a high-sensitivity electrochemical sensor for detecting bisphenol A.
It realizes rapid, sensitive and reliable detection of bisphenol A, with a wide detection range, low detection limit, good repeatability and stability, and is suitable for the detection of actual environmental samples.
Smart Images

Figure CN119591094A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the field of environmental protection technology, and in particular to a porous laser-induced graphene electrode, a preparation method, a product and an application thereof. Background Art
[0002] Phenolic compounds are not only highly toxic and widely available, but can also enter the biological food chain through industrial wastewater, and then enter the human body through the skin surface mucosa, upper respiratory tract and digestive tract, seriously endangering human health. Bisphenol A (BPA) is a phenolic compound that is destructive to endocrine. It is widely used to synthesize materials such as polycarbonate and epoxy resin. According to statistics, about 35.5 million tons of plastic products contain BPA each year in the world, and it is widely used in plastic food containers such as baby bottles and beverage bottles, food plastic packaging and medical devices. It can enter human cells and pose a huge threat to the normal function of the human endocrine system. Long-term exposure to BPA may cause endocrine disorders, precocious puberty in adolescents, liver damage, cardiovascular disease, metabolic disorders and even cancer risks.
[0003] With the continuous improvement of industrial production levels and the people's growing needs for a better life, environmental issues have attracted people's attention. In addition to the above problems, phenolic compounds may also cause water odor, especially when combined with chlorides. Secondly, phenolic substances have a wide range of sources. At present, they mainly come from wastewater discharge from large-scale industrial production such as tar refining and gas production. Although phenolic compounds are indispensable raw materials in the biopharmaceutical and chemical industries, excessive abuse and uncontrolled discharge can only do more harm than good. Therefore, it is of great significance to develop a suitable detection method that can quickly and sensitively detect the BPA content in tap water samples.
[0004] At present, the conventional detection methods for bisphenol A mainly include high performance liquid chromatography, gas chromatography-mass spectrometry, liquid chromatography-mass spectrometry, etc. These methods are accurate and reliable, but they still have disadvantages such as complex pretreatment, long analysis time and expensive instruments. The advantages of electrochemical method such as high sensitivity, simple operation and easy miniaturization have attracted the attention of many researchers. Traditional electrochemical detection technology mostly uses platinum, glassy carbon, gold and other electrodes as working electrodes. However, these electrodes have low sensitivity, poor repeatability, slow electron transfer rate, high overpotential, poor selectivity for detection objects, and electrodes are easily contaminated. The development of functional materials is expected to solve the above problems. Therefore, selecting suitable functional materials to modify the working electrode can improve the sensitivity and selectivity of electrochemical sensors. Summary of the invention
[0005] Based on the above content, the purpose of the present invention is to provide a porous laser-induced graphene electrode, preparation method, product and application. The present invention uses an organic polymer as a precursor, and prepares LIG material on the polymer surface by laser induction technology. Then, a dispersion containing the LIG material is modified on the surface of the base electrode to prepare a working electrode, which is used as an electrochemical sensor for the detection of BPA in actual environmental samples. It has a wide detection range, a low detection limit and a high sensitivity, and has good repeatability and stability.
[0006] In order to achieve the above object, the present invention provides the following technical solutions:
[0007] One of the technical solutions of the present invention is a method for preparing a porous laser-induced graphene electrode, comprising the following steps:
[0008] Step 1. Perform laser direct writing on the surface of the organic polymer film, wait for the surface of the organic polymer film to turn black, and collect the black material;
[0009] Step 2. Dispersing the black material in a solution, and then coating the obtained dispersion on the surface of the base electrode, and drying to obtain the porous laser induced graphene-based electrode.
[0010] The second technical solution of the present invention is a porous laser induced graphene electrode prepared by the above preparation method.
[0011] The third technical solution of the present invention is a sensor, wherein the working electrode is the above-mentioned porous laser induced graphene electrode.
[0012] A fourth technical solution of the present invention is an application of the above sensor in the detection of phenolic organic matter.
[0013] The present invention discloses the following technical effects:
[0014] The LIG prepared in the present invention has a three-dimensional porous structure and a suitable pore size, which is beneficial to the transport of substances and electrons in electrochemical reactions.
[0015] The present invention drips LIG onto the surface of the base electrode, and the target electrode can be obtained by simple dripping and drying, and the preparation process is simple and fast.
[0016] The present invention combines LIG with a substrate electrode to achieve on-site detection of environmental pollutants, and the detection method is simpler and faster.
[0017] The present invention uses LIG as a modified material for the sensor, which enables a lower detection limit (50.68nM) and a wider detection range (100nM to 1.0mM) when detecting bisphenol A, and has good anti-interference and stability. It has good application potential for quantitative analysis of bisphenol A in real environmental samples, with a recovery rate of 98.6% to 105.8%. BRIEF DESCRIPTION OF THE DRAWINGS
[0018] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0019] Figure 1 A and B are scanning electron microscope images of LIG prepared in Example 1 at different magnifications;
[0020] Figure 2 is the XRD pattern of LIG prepared in Example 1;
[0021] Figure 3 A pore size distribution curve and B adsorption isotherm of LIG prepared in Example 1;
[0022] Figure 4 : Cyclic voltammograms of different electrodes in Test Example 1;
[0023] Figure 5 A is the cyclic voltammogram and B is the relationship curve of the LIG / SPE electrode with different LIG modification amounts in Test Example 1;
[0024] Figure 6 Cyclic voltammograms of the LIG / SPE electrode in test example 1 in different buffer solutions A and different pH values B;
[0025] Figure 7 A LSV curve and B peak current vs. concentration of the LIG / SPE electrode used for bisphenol A detection in Test Example 2;
[0026] Figure 8 The anti-interference experimental results of the LIG / SPE electrode in Test Example 2, wherein A is the LSV curve when different interferents are added, and B is the peak current bar graph of LSV when different interferents are added;
[0027] Fig. 9 A stability and B reproducibility bar graph of the LIG / SPE electrode in Test Example 2. DETAILED DESCRIPTION
[0028] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as limiting the present invention, but should be understood as a more detailed description of certain aspects, features, and embodiments of the present invention.
[0029] It should be understood that the terms described in the present invention are only for describing a particular embodiment and are not intended to limit the present invention. In addition, for the numerical range in the present invention, it should be understood that each intermediate value between the upper and lower limits of the scope is also specifically disclosed. The intermediate value in any stated value or stated range, and each smaller range between any other stated value or intermediate value in the described range is also included in the present invention. The upper and lower limits of these smaller ranges can be independently included or excluded in the scope.
[0030] Unless otherwise indicated, all technical and scientific terms used herein have the same meanings as those generally understood by those skilled in the art. Although the present invention describes only preferred methods and materials, any methods and materials similar or equivalent to those described herein may also be used in the implementation or testing of the present invention. All documents mentioned in this specification are incorporated by reference to disclose and describe the methods and / or materials associated with the documents. In the event of a conflict with any incorporated document, the content of this specification shall prevail.
[0031] It will be apparent to those skilled in the art that various modifications and variations may be made to the specific embodiments of the present invention description without departing from the scope or spirit of the present invention. Other embodiments derived from the present invention description will be apparent to the skilled artisan. The present invention description and examples are exemplary only.
[0032] The words “include,” “including,” “have,” “contain,” etc. used in this document are open-ended terms, meaning including but not limited to.
[0033] In the present invention, room temperature means a temperature of 20-40°C.
[0034] The first aspect of the present invention provides a method for preparing a porous laser-induced graphene electrode, comprising the following steps:
[0035] Step 1. Perform laser direct writing on the surface of the organic polymer film, wait for the surface of the organic polymer film to turn black, and collect the black material (referred to as LIG);
[0036] Step 2. Dispersing the black material in a solution, and then coating the obtained dispersion on the surface of the base electrode, and drying to obtain the porous laser induced graphene-based electrode.
[0037] The LIG prepared by the present invention has a three-dimensional porous structure, and the pore size range is mainly concentrated around 5nm and 40nm.
[0038] In some embodiments of the present invention, the organic polymer film is first fixed on a substrate material and then laser direct writing is performed. The present invention does not specifically limit the selection of the substrate material, and substrate materials commonly used by those skilled in the art can be selected, such as glass substrate, polystyrene, polysulfone ether or cellulose film.
[0039] In some embodiments of the present invention, the organic polymer film is a polyimide film, a polyetherimide film, a polyetheretherketone film, a polyetherphenol film, a phenolic resin film or a cellulose film, preferably a polyimide film.
[0040] In some embodiments of the present invention, the parameters of the laser direct writing are set as follows: wavelength 450nm, laser output power 0.5W-3.2W, scanning speed 0.5-10cm / s.
[0041] In some embodiments of the present invention, the parameters of the laser direct writing are set as follows: wavelength 450nm, laser output power 2.2W, scanning speed 0.5cm / s.
[0042] The present invention strictly limits the laser direct writing parameters so that the sensor finally obtained has a large detection range for bisphenol A and a low detection limit, and can quickly and sensitively detect the BPA content in the water sample.
[0043] In some embodiments of the present invention, the concentration of the black material in the dispersion is 0.1 mg / mL-5.0 mg / L. The present invention does not specifically limit the method of dispersing the black material in the solvent, and the commonly used technical means by those skilled in the art can be selected, such as ultrasonic dispersion.
[0044] In some embodiments of the present invention, the solution used to disperse the black material is a Nafion solution (perfluoropolystyrene sulfonic acid solution); the concentration of the Nafion solution is 0.5wt%. The present invention does not specifically limit the preparation method of the Nafion solution, and conventional technical means of those skilled in the art can be used, for example: dissolving Nafion in a mixed solution of water and ethanol.
[0045] In some embodiments of the present invention, the concentration of the black material in the dispersion is 0.5 mg / L.
[0046] In some embodiments of the present invention, the substrate electrode is a glassy carbon electrode, a gold electrode, a carbon paste electrode or a screen-printed electrode; when the dispersion is coated on the surface of the substrate electrode, the amount of the dispersion used is 84.9 μL / cm 2 To 311.4μL / cm 2 The active surface of the substrate electrode in contact with the electrolyte is a circle with a diameter of 3 mm, that is, the amount of dispersion is 7.07 mm 2The amount of active working area of the substrate electrode is 6-22 μL (preferably 16-20 μL), which is converted to 84.9 μL / cm 2 To 311.4μL / cm 2 The present invention does not specifically limit the coating method, and conventional techniques used by those skilled in the art may be used, such as drip coating.
[0047] In some embodiments of the present invention, before coating the obtained dispersion on the surface of the substrate electrode, the step of cleaning the substrate electrode with water and ethanol is also included.
[0048] In some embodiments of the present invention, the drying method is natural drying at room temperature, for example, drying at room temperature of 20-40° C. for 30-240 min.
[0049] A second aspect of the present invention provides a porous laser induced graphene electrode prepared by the preparation method described in the above technical solution.
[0050] A third aspect of the present invention provides a sensor, wherein the working electrode is the above-mentioned porous laser induced graphene electrode.
[0051] In the sensor, the working condition parameters of the working electrode are set as follows: the working pH range is 4-9 (preferably pH=5), and the buffer solution is BR, HAc-NaAc, PBS or Tris-HCl (preferably PBS).
[0052] A fourth aspect of the present invention provides an application of the above sensor in the detection of phenolic organic matter.
[0053] In some embodiments of the present invention, the phenolic organic compound is bisphenol A.
[0054] The sensor provided by the present invention is used to detect bisphenol A, with a detection range of 100nM to 1.0mM and a detection limit of 50.68nM. When the content of bisphenol A in actual samples is measured, the recovery rate of the spiked solution is 98.6% to 105.8%.
[0055] In order to better understand the present invention, the content of the present invention is further explained below in conjunction with the embodiments, but the content of the present invention is not limited to the following embodiments.
[0056] The technical solutions described in the present invention, unless otherwise specified, are all conventional solutions in the art, and the reagents or raw materials used, unless otherwise specified, are purchased from commercial channels or have been disclosed.
[0057] The active working area of the substrate electrode used in the examples is a circle with a diameter of 3 mm.
[0058] Example 1
[0059] Step 1. Fix the polyimide film on a glass plate and use a laser direct writer with a wavelength of 450nm (laser output power of 2.2W, scanning speed of 0.5cm / s) to print on the surface of the polyimide film. It is found that the yellow film surface turns black. Carefully scrape off the black material to obtain LIG.
[0060] Step 2. Use the screen-printed electrode (SPE) as the base electrode, clean the screen-printed electrode with ultrapure water and ethanol respectively to obtain a treated base electrode; then accurately weigh 1.0 mg of LIG solid into a small sample tube, add 2.0 mL of water and ethanol as a mixed solvent to prepare a 0.5% Nafion solution, and ultrasonically disperse for 10 minutes to obtain a 0.5 mg / mL LIG dispersion. Take 18.0 μL of the above dispersion and drop it on the surface of the pre-treated screen-printed electrode, dry it at 25°C for 120 minutes, and obtain LIG / SPE (i.e., based on porous laser-induced graphene electrode).
[0061] Figure 1 This is a scanning electron microscope image of the LIG prepared in Example 1. It can be clearly seen from the image that the prepared LIG has a three-dimensional network structure and has pores of different sizes.
[0062] Figure 2 This is the XRD image of LIG prepared in Example 1. It can be seen from the figure that there is a relatively wide characteristic diffraction peak of the graphite 002 crystal plane at about 25°, indicating that LIG has a certain degree of graphitization.
[0063] Figure 3 The adsorption isotherm and pore size distribution diagram of LIG prepared in Example 1 show that LIG has a typical pore structure, and its pore size is mainly distributed around 5 nm and 40 nm. This is mainly due to the gas escape in the organic matter and the reconstruction of the carbon framework during the laser printing process.
[0064] Test Example 1
[0065] The electrochemical behavior of BPA on LIG / SPE was investigated by cyclic voltammetry (CV) in 1.0 mM bisphenol A and 0.1 M PBS (pH = 5.0) with a scan rate of 100 mV / s in the range of 0.3 to 1.2 V. Figure 4 , 5 ,CV graph,curve in 6;
[0066] LIG / SPE was used to quantitatively and qualitatively analyze BPA by linear sweep voltammetry (LSV) at a scan rate of 100 mV / s in the potential range of 0.3 to 1.2 V. Figure 7 , 8 ,LSV graph,curve in 9.
[0067] The porous laser-induced graphene electrode prepared in Example 1 was used for bisphenol A detection.
[0068] Cyclic voltammetry (CV) was used to electrochemically test BPA using SPE and LIG / SPE. Figure 4 As shown (in the figure, curve a represents the CV of LIG / SPE in PBS without BPA, curve b represents the CV of bare SPE in PBS containing BPA, and curve c represents the CV of LIG / GCE in BPA-PBS buffer solution). When there is no BPA in the solution, no obvious redox peak appears on LIG / SPE (curve a). In a PBS solution containing 1.0 mM BPA, a smaller oxidation peak is detected by the unmodified SPE, with a peak potential of 0.82 V and a current of about 10 μA. It can be determined that the oxidation peak corresponds to the electrochemical oxidation process of BPA (curve b). A more obvious oxidation peak appears on the CV curve of LIG / SPE (curve c), with a peak current of about 45 μA, which is about 4.5 times that of SPE. This shows that the modification of LIG can significantly increase the electrochemical oxidation signal of BPA, which may be due to the large specific surface area and excellent conductivity of LIG.
[0069] Figure 5 The CV graphs and relationship curves of LIG / SPE electrodes with different LIG modification amounts are shown in Figure 2. The modification amount of LIG will affect the electrochemical oxidation signal of BPA. When the LIG drop coating volume f is 6μL, 8μL, 10μL, 14μL, 16μL, 18μL, 20μL, and 22μL, the CV curves of BPA on LIG / SPE are shown in Figure 2. Figure 5 As shown in A. It can be found that when the LIG modification volume is in the range of 6μL-18μL, the oxidation peak of BPA gradually increases with the increase of LIG modification amount ( Figure 5 (B) When the LIG modification volume is greater than 18 μL, the oxidation peak of BPA begins to decrease. This may be because excessive LIG modification will hinder the diffusion of electrolytes on the electrode surface, which is not conducive to the occurrence of electrochemical reactions. Therefore, the optimal drop coating volume of LIG dispersion is 18 μL.
[0070] Figure 6 The cyclic voltammograms of the LIG / SPE electrode prepared in Example 1 in different buffer solutions and at different pH values; Figure 6 As shown in A, 1.0 mM BPA solution was prepared with BR, HAc-NaAc, PBS, and Tris-HCl buffer solutions, and the CV curves of LIG / SPE in the mixed solutions were recorded. It can be found that in PBS solution, the oxidation peak current of LIG / SPE is the highest and most obvious. The CV method was used to investigate the effect of pH value of PBS solution on BPA detection. Figure 6Figure B is the CV curve of LIG / SPE in BPA mixed solution with pH values of 4.0-9.0. The peak shape of the cyclic voltammogram is poor in the solution pH range of 7.0-9.0, and the oxidation peak current is small; while the peak current is the largest at pH 5.0.
[0071] Example 2
[0072] The same as Example 1, the only difference is that the polyimide membrane is replaced by a cellulose membrane to obtain LIG / SPE (i.e. based on porous laser induced graphene electrode).
[0073] Test Example 2
[0074] The LIG / SPE electrode prepared in Example 2 was used for bisphenol A detection, and its selectivity, anti-interference ability, etc. were studied.
[0075] Figure 7 The LSV curve and the relationship between the peak current and the concentration of the LIG / SPE electrode used in Example 2 for the detection of bisphenol A are shown in Figure 2. The electrochemical detection of 100nM to 1.0mM BPA solution was performed using the LSV method. The results are shown in Figure 2. Figure 7 As shown in A. As the concentration of BPA increases, the oxidation peak current gradually increases, and I p It has a good linear relationship with the concentration C ( Figure 7 In B), the linear regression equation is: p1 (μA)=764.8C(mM)+1.302(R 2 =0.960, 100nM~10μM); I p2 (μA)=83.88C(mM)+11.398(R 2 =0.994, 10μM~1.0mM), and the detection limit (LOD) is 50.68nM (3S / N). The reason for the two-stage linear equation may be that when the BPA concentration is low (100nM~10μM), there are relatively more active sites on the LIG / SPE surface, and BPA can react quickly on the modified electrode surface, so the slope is higher and the reaction speed is faster; when the BPA concentration is high (10μM~1.0mM), the active sites on the LIG / SPE surface are occupied by BPA, so the active sites on the LIG / SPE surface are relatively small, the slope of the linear equation becomes smaller, and the sensitivity becomes lower.
[0076] Figure 8The results of the anti-interference experiment of the LIG / SPE electrode in Example 2 are shown in Figure 2. The LSV method was used to determine the effects of some common interfering substances on the performance of LIG / SPE in detecting 1.0 mM BPA. Equal concentrations of interfering substances such as KCl, NaCl, dichlorvos, diuron, fenitrothion, and glyphosate were added to the 1.0 mM BPA solution, and the LSV curve of LIG / SPE in the mixed solution was detected. The oxidation current value of BPA is shown in Figure 2. Figure 8 As shown, the calculated relative standard deviations are all within 5%. The experimental results show that the above-mentioned substances do not interfere with the detection of BPA, indicating that LIG / SPE has good anti-interference ability.
[0077] Fig. 9 The stability and reproducibility bar graph of the LIG / SPE electrode of Example 2. Five identical LIG / SPEs were prepared at the same time, and LSV curves were collected in the same BPA solution. The results are shown in FIG. Fig. 9 As shown in Figure A (in Figure A, 1, 2, 3, 4, and 5 represent the five prepared LIG / SPEs), the RSD of the oxidation peak current is 2.56%, indicating that LIG / SPE has good reproducibility. The prepared LIG / SPE was further placed in a 4°C refrigerator for 6 consecutive days and tested once a day in a BPA solution. The results are shown in Figure 1. Fig. 9 As shown in B. Through image comparison and data analysis, the BPA oxidation current detected after 6 consecutive days is still 80.24% of the original, indicating that the sensor has good reproducibility and stability and has good application potential.
[0078] The present invention also conducted the same experiment as in Test Example 2 on the LIG / SPE prepared in Example 1. The results show that the LIG / SPE electrode prepared using the polyacetimide film as a raw material in Example 1 has good anti-interference, good repeatability and stability.
[0079] The present invention also verifies the performance of the LIG / SPE electrode prepared when the raw materials are polyetherimide film, polyetheretherketone film, polyetherphenol film and phenolic resin film, and the results are similar to those of Example 1 and Example 2. The LIG / SPE electrodes prepared from the raw materials polyetherimide film, polyetheretherketone film, polyetherphenol film and phenolic resin film have good anti-interference, good repeatability and stability, and have high sensitivity to bisphenol A.
[0080] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a porous laser-induced graphene electrode, characterized in that: The following steps are involved: Step 1. Perform laser direct writing on the surface of the organic polymer film, wait for the surface of the organic polymer film to turn black, and collect the black material; Step 2. Dispersing the black material in a solution, and then coating the obtained dispersion on the surface of the base electrode, and drying to obtain the porous laser induced graphene-based electrode.
2. The method for preparing a porous laser-induced graphene electrode according to claim 1, characterized in that: The organic polymer film is a polyimide film, a polyetherimide film, a polyetheretherketone film, a polyetherphenol film, a phenolic resin film or a cellulose film.
3. The method for preparing a porous laser-induced graphene electrode according to claim 1, characterized in that: The parameters of the laser direct writing are set as follows: wavelength 450nm, laser output power 0.5W-3.2W, scanning speed 0.5-10cm / s.
4. The method for preparing a porous laser-induced graphene electrode according to claim 1, characterized in that: The concentration of the black material in the dispersion is 0.1 mg / mL-5.0 mg / L.
5. The method for preparing a porous laser-induced graphene electrode according to claim 1, characterized in that: The base electrode is a glassy carbon electrode, a gold electrode, a carbon paste electrode or a screen-printed electrode; when the dispersion is coated on the surface of the base electrode, the amount of the dispersion used is 84.9 μL / cm 2 To -311.4μL / cm 2 .
6. A porous laser-induced graphene electrode prepared by the preparation method according to any one of claims 1 to 5.
7. A sensor, characterized in that: The working electrode is the porous laser induced graphene electrode as described in claim 6.
8. Use of the sensor according to claim 7 in the detection of phenolic organic substances.
9. Application of the sensor according to claim 8 in the detection of phenolic organic matter, characterized in that: The phenolic organic compound is bisphenol A.
Citation Information
Patent Citations
Application of electrochemical sensor prepared from graphene material in bisphenol A detection
CN103979531A
Laser induced graphene hybrid materials for electronic devices
CN107206741A
Laser engraving preparation method of high-conductivity graphene film array
CN109421402A
Electron beam induced patterned graphene and preparation method thereof
CN110980704A
Laser-induced graphene-based sensor as well as preparation method and application thereof
CN118191054A